2006
DOI: 10.1128/aac.50.1.34-37.2006
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis Study of Imipenem Distribution in the Intraperitoneal Fluid of Rats with or without Experimental Peritonitis

Abstract: The purpose of this study was to extend the use of microdialysis to the investigation of antibiotic distribution into the intraperitoneal fluid of rats with or without peritonitis. Microdialysis probes were inserted into the jugular vein and peritoneal cavity of control rats or rats with intra-abdominal sepsis (n ‫؍‬ 8 in each group) induced by cecal ligation and punctures. Imipenem (IPM) probe recoveries were determined in each rat by retrodialysis by drug. IPM was infused intravenously at a dose of 30 mg · k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
11
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
4
11
1
Order By: Relevance
“…These results are consistent with data previously published by our group (7,10). Mean values of IPM blood pharmacokinetic parameters (clearance and volume of distribution) were close to those previously reported (10) but with more interindividual variability.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…These results are consistent with data previously published by our group (7,10). Mean values of IPM blood pharmacokinetic parameters (clearance and volume of distribution) were close to those previously reported (10) but with more interindividual variability.…”
supporting
confidence: 83%
“…The present study confirms that even in the presence of infection, unbound IPM AUCs are not statistically different in blood, lung, and muscle, still consistent with theory. Similarly a lack of effect of infection on IPM distribution in peritoneal fluid was recently observed using an experimental model of peritonitis (7). Yet the present observation is not consistent with the findings of a previous study conducted with infected critically ill patients (16).…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…A pharmacokinetic model with peripheral elimination, consistent with the degradation of meropenem observed ex vivo in the PF of other patients, was developed to successfully fit the data. However, in a previous intraperitoneal-microdialysis study in rats, we observed that unbound imipenem concentration-versus-time profiles were almost always superimposed in blood and PF, both in control rats and in rats with an experimental model of peritonitis by cecal ligation and puncture (6). Although it should be confirmed experimentally, the same observation would most likely be made with the more stable meropenem (4).…”
mentioning
confidence: 55%
“…Two CMA/20 probes (polycarbonate; membrane length, 10 mm; 20,000-Da cutoff; CMA microdialysis; Phymep, Paris, France) were inserted into the right jugular vein and into the central part of the pancreatic gland within the peritoneal cavity, respectively. The microdialysis study was conducted as previously described (6). After retrodialysis by drug period, in which probes were perfused with Ringer solution (Phymep, Paris, France) containing imipenem at 10 g ⅐ ml Ϫ1 (Tienam; Merck Sharp & DohmeChibret Laboratories), and a washout period, the rats received an intravenous infusion of imipenem at a dose of 30 mg ⅐ kg ) and directly analyzed as previously described (6).…”
mentioning
confidence: 99%